Penerapan Klausul Non-Refundable Tiket Penerbangan Haji Terhadap Konsumen yang Menderita Kerugian - Pitang, Govara Remeina; Sudiro, Amad (Universitas Muhammadiyah Ponorogo, 2025)
The development of the aviation industry, particularly in the implementation of the Hajj pilgrimage, encourages airlines to implement various clauses in transportation agreements, one of which is the non-refundable clause. The problem faced is how to provide legal protection for those who suffer losses due to the implementation of non-refundable clauses in flight tickets. The type of research used is normative juridical legal research. The results of the study indicate that non-refundable clauses in air transportation agreements are problematic. Non-refundable clauses in flight tickets are standard clauses that have the potential to harm consumers because they eliminate the right to a refund. Decision Number: 310/Pdt.G/2023/PN Jkt.Brt emphasizes that legal protection for consumers can be realized in court through an assessment of the validity of the clause, in order to create a balance of rights between business actors and consumers.